Mental health in elite athletes: a systematic review of suicidal behaviour as compared to the general population - Gill, V. S.; Sullivan, G.; Stearns, H.; Tummala, S. V.; Haglin, J. M.; Economopoulos, K. J.; Marks, L.; Chauhan, M. (Sports Medicine, 2024)
Background and Objective: Previous systematic reviews on mental health in athletes have found athletes to be at a potentially increased risk for mental health diagnoses compared to the public. Multiple cross-sectional studies have examined suicide behaviour within different athlete populations, but there is a need for a comprehensive review to synthesize and identify risk factors and epidemiology regarding suicide behaviour in the elite athlete population, especially as it compares to the general population. Methods: A systematic literature search was performed in MEDLINE, EMBASE, Scopus, and Web of Science from 1990 to January 2023. Inclusion criteria included original peer-reviewed research articles examining suicidal ideation, suicide attempt, or suicide completion within elite athlete populations. Exclusion criteria included athletes participating in high-school or Paralympic level sports, studies that did not report results regarding elite athletes and non-athletes separately, and non-peer reviewed work. All studies were screened for inclusion by two independent reviewers. The primary outcome variables extracted from included studies included rates, risk factors, and protective factors for suicide behaviour. The study quality and risk of bias was evaluated for each study using the Joanna-Briggs Institute (JBI) critical appraisal tools. Results: Of the 875 unique studies identified, 22 studies, all of which were cross-sectional in nature, met the inclusion criteria. Seven studies evaluated previous athletes, 13 studies evaluated current athletes, and two studies included a combination of previous and current athletes. Seven studies involved varsity college athletes, nine involved professional athletes of various sports, and six focused on international or Olympic level athletes. The rate of suicidal ideation in professional athletes ranged from 6.9 to 18% across four studies, while the rate in collegiate athletes ranged from 3.7 to 6.5% across three studies. Ten studies compared athletes to the general population, the majority of which found athletes to be at reduced risk of suicidal ideation, suicide attempt, and suicide completion. Only one study found athletes to have increased rates of suicide compared to matched non-athletes. Risk factors for suicide behaviour identified across multiple studies included male sex, non-white race, older age, and depression. Player position, athletic level, sport played, and injuries showed trends of having limited effect on suicide behaviour risk. Conclusion: This review suggests that elite athletes generally demonstrate reduced risk of suicidal ideation, suicide attempt, and suicide completion compared to the general population. Coaches should remain aware of specific factors, such as male sex, non-white race, and higher athletic level, in order to better identify at-risk athletes. Limitations of this review include the heterogeneity in the methodology and athlete populations across the included studies. Therefore, future targeted research is essential to compare suicide behaviour between sports and identify sport-specific suicide risk factors.